(untitled) (Al-Qamar, 2018)
Monetary system is the most important part of everyday life of human kind. As known that money is considered as one of the basic and necessary need of human beings so ways of earning money which are prohibited and permitted in Islamic Shariah are explicitly described. ALLAH Almighty created humankind and bestowed him the central and most esteemed position in the creational arena. Our lord has bestowed us with His final revelation in form of Al-Quran and its interpretation in form of Sunnah. The muslim jurists have developed their jurisprudence to derive injunctions from the primary sources of shariah; the four principles. The concept and theory of Expediency (Maṣliḥat) is admitted and endorsed among all famous juristic schools of Islam. This paper revolves around this question that to what extent this principle has been observed in contemporary financial and fiscal contracts. Opting analytical and somehow critical method the non-interest based banking system and the sale and purchase of shares have been brought under discussion to find out the answer of said question. The authors have concluded that the contemporary non-interest-based banking system is difficult to be justified within the juristic limits except with the principle of expediency. However, transactions in stock markets have been justified by it supporters under the juristic principles and it has no need to align with the principle of expediency. Moreover, the authors are of this view that some more in-depth research on the character of this principle of expediency in the context of modern Ijtihad is a dire need of time to fix the utility of this principle in solving the challenges of modern era.